The Last Hurrah: Thomas Baines and the expedition to the coronation of Cetshwayo kaMpande, Zululand, 1873 - Stiebel, Lindy; Carruthers, Jane (Southern African Humanities, 2019)
In 1873, John Thomas Baines joined the retinue of Theophilus Shepstone, then Secretary for Native Affairs in the colony of Natal, travelling into Zululand to ‘crown’ Cetshwayo as Zulu king. We argue that this was Baines’s ‘Last Hurrah’: it was his last adventure and he died two years later. The life and work of Baines—artist, explorer, and diarist—have been well recorded by scholars, but here we highlight two aspects of his final expedition that have not previously been given detailed attention. As assigned Special Correspondent to the Natal Mercury, Baines wrote comprehensive descriptions of the events in which he took part, and here we subject these to close literary critique and scrutiny. Moreover, Baines’s participation in the ‘coronation’ encouraged him to produce a detailed map of Zululand, now housed in the Royal Geographical Society in London. This too has not been published or closely examined, and our analysis sheds light on the geopolitical state of the subcontinent, as well as on the biography of Baines. KEY WORDS: John Thomas Baines, history of Natal, KwaZulu-Natal, Zulu history, history of cartography, Natal Mercury.